The women in the castle [compact disc, unabridged] - Shattuck, Jessica (Harper Audio, 2017)
At the end of World War II, Marianne von Lingenfels offers shelter to two widows of fallen resistance fighters and their children in a formerly majestic Bavarian castle that was once host to German aristocrats.